Expression of HMGB1 and HMGN2 in gingival tissues, GCF and PICF of periodontitis patients and peri-implantitis - Xie,Ping (2011)
High mobility group chromosomal protein B1 (HMGB1) and N2 (HMGN2), two members of High mobility group (HMG) family, play important role in inflammation. The purposes of this study were to investigate the expression of HMGB1 and HMGN2 in periodontistis. The expression of HMGB1 and HMGN2 mRNA in gingival tissues and gingival crevicular fluid (GCF) in chronic periodontitis (CP), generalized aggressive periodontitis (G-AgP) patients and healthy subjects was detected by real-time PCR. The protein level of HMGB1 and HMGN2 in peri-implant crevicular fluid (PICF), peri-implant crevicular fluid of peri-implantitis (PI-PICF) and normal patients was determined by Western blotting. Furthermore, IL-1β, IL-6, IL-8, TNF-α and HMGB1 levels in GCF, PI-PICF and healthy-PICF samples from different groups were determined by ELISA. HMGN2 expression was increased in inflamed gingival tissues and GCF from CP and G-ApG groups compared to control group. HMGB1 expression was the highest in the gingival tissues and GCF from CP patients and was accompanied by increased concentrations of IL-1β, IL-6, IL-8 proinflammaory cytokines. To our knowledge, this is the first study reporting that the expression of HMGB1 and HMGN2 was increased in the gingival tissues and GCF in CP and G-AgP and the PICF in PICF. Our data suggest that HMGB1 may be a potential target for the therapy of periodontitis and PI.